2007
DOI: 10.1007/s10806-007-9043-z
|View full text |Cite
|
Sign up to set email alerts
|

Will Consumers Save The World? The Framing of Political Consumerism

Abstract: An active ethically conscious consumer has been acclaimed as the new hero and hope for an ethically improved capitalism. Through consumersÕ ''voting'' at the checkout, corporations are supposed to be held accountable for their conduct. In the literature on political consumerism, this has mainly been approached as political participation and governance. In this article, we do a critical review of this literature. We do so by questioning the existence of what we call a ''generic active consumer model.'' At the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 15 publications
3
84
0
5
Order By: Relevance
“…One can speculate that the heightened awareness of the contribution that food miles potentially make to global warming is entering into food purchasing decisions. Consumers may be moving from considering buying local as solely a pragmatic issue of getting fresher food and supporting local economies, to encompassing larger sociopolitical issues where impacts can be made through responsible consumerism (Jacobsen & Dulsrud, 2007;Vermeir & Verbeke, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One can speculate that the heightened awareness of the contribution that food miles potentially make to global warming is entering into food purchasing decisions. Consumers may be moving from considering buying local as solely a pragmatic issue of getting fresher food and supporting local economies, to encompassing larger sociopolitical issues where impacts can be made through responsible consumerism (Jacobsen & Dulsrud, 2007;Vermeir & Verbeke, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Realizar la compra en el mercado y recibir el ticket puede ser interpretado simbólicamente como el acto de votar, de tal forma que a través del "voto" de los consumidores en las cajas, las empresas sienten que tienen que rendir cuentas (Jacobsen y Dulsrud, 2007;Johnston, 2008). Así "en el momento en que se usa el mercado como forma de acción política, la empresa ha de actuar en consecuencia y asumir el papel de actor político.…”
Section: Actores Involucrados En Los Contextos De Participaciónunclassified
“…La investigación futura debe identificar las conexiones entre el consumo con conciencia social y la ciudadanía democrática (Dulsrud y Jacobsen, 2007). En la actualidad, los debates teóricos giran en torno a la idea de que la búsqueda de un futuro más sostenible pasa por el "cambio de comportamiento" de un número importante de personas en la sociedad.…”
Section: "Consumocracia" O El Empoderamiento De Los Consumidores Anteunclassified
“…However, Jacobsen and Dulsrud [29] found that consumers do not often have enough information about the politics beyond products to make informed political consumerist choices. This is the jumping off point for the rest of our analysis.…”
Section: Sustainability 2011 4 2154mentioning
confidence: 99%
“…How must consumer food information systems be redesigned to leverage the citizen-consumer phenomenon and advance government objectives around health and sustainability? Given that health and sustainability are collective good objectives, we follow Johnston's interpretation that draws a clear distinction between consumerism's "maximization of individual self-interest through commodity choice," and citizenship based on the prioritization of "the collective good," which "emphasizes responsibility to ensure the survival and wellbeing of others-human and non-human" ( [29], p. 243). This is an important distinction because a significant assumption of the current system is that individual self-optimization generates wider societal value.…”
Section: Sustainability 2011 4 2154mentioning
confidence: 99%